Analisis Perbandingan Jumlah Tenaga Kesehatan dengan Jumlah Fasilitas Kesehatan, di Kabupaten Rokan Hulu - Rahma, Hafidzah Isna (Maliki Interdisciplinary Journal, 2025)
This study discusses the comparison of the number and distribution of healthcare personnel (excluding doctors) and healthcare facilities in Rokan Hulu Regency in 2023 and 2024. Based on data from BPS Rokan Hulu, the number of healthcare personnel increased from 1,402 in 2023 to 1,923 in 2024. However, this increase has not fully addressed the actual needs in several districts, particularly in areas such as Kepenuhan Hulu, Pendalian IV Koto, and Pagaran Tapah Darussalam, which still show low distribution of healthcare personnel. This study also analyzes the number of healthcare facilities, which reached 190 units in 2024, and the challenges in aligning workforce distribution with facility availability. Recommendations are provided in the form of redistribution strategies, increased incentives, and stakeholder collaboration to achieve equitable healthcare services.